Aerobic and anaerobic fitness levels of pre-professional contemporary dancers: An exploration of 2 dance-specific field tests - Tiemens, A.; van Rijn, R. M.; Koes, B. W.; Stubbe, J. H. (Journal of Dance Medicine & Science, 2024)
Introduction The primary aim of this study was to present descriptive heart rate (HR), heart rate recovery (HRR) and RPE data for the DAFT and HIDT within one sample of contemporary dance students. The second aim was to explore if objective (HR) and subjective (RPE) data were correlated between tests.